Investigation of seismic resistant structures with various moment-resisting frame systems and pushover analysis - Putra, Oky Bima; Ramadhan, Ilham Dwiputra; Rosyidah, Anis; Saputra, Jonathan; Sucita, I Ketut (SINERGI, 2024)
Earthquakes are a serious threat in the construction of multi-storey buildings in Indonesia, which are divided into several seismic design categories. The design of seismic-resistant buildings requires the management of plastic hinges to reduce seismic loads. The aspects of seismic-resistant structural design in Indonesia are regulated by SNI 1726:2019, SNI 1727:2020, and SNI 2847:2019. Intermediate Moment Resisting Frame System (IMRFS) and Special Moment Resisting Frame System (SMRFS) are used based on seismic category and earthquake intensity. Pushover analysis is used to analyze the structures behavior when exposed to seismic loads. This research designs seismic resistant structures with IMRFS and SMRFS at different locations with the aim of assessing structural performance and gaining reinforcement to the concrete ratio, which is relevant for the design and construction of multi-storey buildings in Indonesia. The results of this research are the structural performance levels, reinforcement volume, concrete volume, and the reinforcement to concrete volume ratio. Both IMRFS and SMRFS reached Immediate Occupancy to Life Safe performance levels after the earthquake because their monitored displacement was not significantly different. The structural failure modes of both systems meet the Strong Column–Weak Beam requirements. The distribution of plastic hinges also remains in the Immediate Occupancy category.